impA, a Gene Coding for an Inner Membrane Protein, Influences Colonial Morphology of Actinobacillus actinomycetemcomitans - Mintz, Keith P. (American Society for Microbiology, 2000)
Directed mutagenesis of a gene coding for a membrane protein of the periodontopathogen Actinobacillus actinomycetemcomitans was achieved by conjugation. The gene was disrupted by insertion of an antibiotic cassette into a unique endonuclease restriction sequence engineered by inverse PCR. The disrupted gene was cloned into a conjugative plasmid and transferred from Escherichia coli to A. actinomycetemcomitans. The allelic replacement mutation resulted in the loss of a 22-kDa inner membrane protein. The loss of this protein (ImpA) resulted in changes in the outer membrane protein composition of the bacterium. Concurrent with the mutation in impA was a change in the pattern of growth of the mutant bacteria in broth cultures. The progenitor bacteria grew as a homogeneous suspension of cells compared to a granular, autoaggregating adherent cell population described for the mutant bacteria. These data suggest that ImpA may play a regulatory role or be directly involved in protein(s) that are exported and associated with colony variations in A. actinomycetemcomitans.